2015
DOI: 10.1007/7854_2015_368
|View full text |Cite
|
Sign up to set email alerts
|

New World Tryptamine Hallucinogens and the Neuroscience of Ayahuasca

Abstract: New World indigenous peoples are noted for their sophisticated use of psychedelic plants in shamanic and ethnomedical practices. The use of psychedelic plant preparations among New World tribes is far more prevalent than in the Old World. Yet, although these preparations are botanically diverse, almost all are chemically similar in that their active principles are tryptamine derivatives, either DMT or related constituents. Part 1 of this paper provides an ethnopharmacological overview of the major tryptamine-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 35 publications
1
54
1
1
Order By: Relevance
“…The authors interpreted their findings in terms of increased feed-forward or bottom-up information transfer and decreased feed-back or top-down control. Our findings would support 5-HT2A agonism as a key mechanism in the modification of brain dynamics induced by ayahuasca (McKenna and Riba, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…The authors interpreted their findings in terms of increased feed-forward or bottom-up information transfer and decreased feed-back or top-down control. Our findings would support 5-HT2A agonism as a key mechanism in the modification of brain dynamics induced by ayahuasca (McKenna and Riba, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…A yahuasca is a hallucinogenic botanical brew prepared by decoction of the bark of the vine Banisteriopsis caapi together with the leaves of the shrub Psychotria viridis. 1 Banisteriopsis caapi contains β-carboline alkaloids (harmine, tetrahydroharmine, and harmaline) that act as reversible inhibitors of monoamine oxidase(MAO)-A, whereas P. viridis is rich in N,N-dimethyltryptamine (DMT), n hallucinogenic tryptamine that acts as a 5-HT 1A/2A/2C agonist. 1,2 The psychoactive effects of ayahuasca are produced by a combined action of β-carbolines and DMT: because DMT is metabolized by MAO-A in the gut and liver, peripheral MAO-A inhibition by β-carbolines allows DMT to reach systemic circulation and the brain, where it acts at frontal and paralimbic areas.…”
mentioning
confidence: 99%
“…1 Banisteriopsis caapi contains β-carboline alkaloids (harmine, tetrahydroharmine, and harmaline) that act as reversible inhibitors of monoamine oxidase(MAO)-A, whereas P. viridis is rich in N,N-dimethyltryptamine (DMT), n hallucinogenic tryptamine that acts as a 5-HT 1A/2A/2C agonist. 1,2 The psychoactive effects of ayahuasca are produced by a combined action of β-carbolines and DMT: because DMT is metabolized by MAO-A in the gut and liver, peripheral MAO-A inhibition by β-carbolines allows DMT to reach systemic circulation and the brain, where it acts at frontal and paralimbic areas. [1][2][3] Preclinical, observational, and experimental studies in healthy volunteers suggest that ayahuasca has antidepressive properties, 4 and we recently reported that administration of ayahuasca to 6 patients with recurrent major depressive disorder (MDD) was associated with fast-acting and enduring antidepressive effects.…”
mentioning
confidence: 99%
“…DMT ( 168 ) is the active component in ayahuasca. 115 Its biosynthesis occurs within plants via the shikimate pathway. 116 This pathway is also responsible for the biosynthesis of the amino acid tryptophan as well as various indole alkaloid precursors.…”
Section: The Hallucinogensmentioning
confidence: 99%